Agile Adoption and its Impact on Inter-team Technical Coordination and Delivery Perception in Hybrid IT Organisations - Fox, Elsa (My University, 2025)
This study investigates how agile adoption influences inter-team technical coordination and stakeholder perception of delivery in hybrid IT organisations where agile and traditional methodologies coexist. Through a single case study within a multinational cosmetics company, seven semi-structured interviews were conducted with stakeholders across different coordination interfaces, using an integrated framework combining Thompson’s Interdependence Theory and Freeman’s Stakeholder Theory. The findings reveal that hybrid IT environments develop sophisticated coordination mechanisms beyond traditional approaches: standardisation through documentation and quality standards, planning through release-based coordination and roadmapping, and mutual adjustment through over-communication strategies and small-group meetings. Emergent hybrid-specific mechanisms include Product Owner translation roles, branch-based integration strategies, and definition of done alignment processes. Regarding stakeholder perception, timeline adherence emerges as the dominant success factor across all stakeholder groups, transcending methodological preferences. Stakeholders develop multi-criteria quality assessment frameworks while requiring transparency about progress and risk to maintain confidence in hybrid environments. This research extends Thompson’s theory by identifying hybrid-specific coordination mechanisms and contributes to Stakeholder Theory by examining perception formation across multiple delivery methodologies. The findings provide practical guidance for coordination design and stakeholder management in hybrid IT organisations.
Keywords: Agile Delivery, Hybrid IT Environments, Technical Coordination, Delivery Perception, Interdependence Theory, Stakeholder Theory